Analisis Postur Kerja dengan Metode Rapid Entire Body Assissment (REBA) - Darsini; Reza Tania Achmadi (Indonesian Society of Applied Science, 2021)
Physical activity related to work activities on production operators is one of the jobs that needs attention. Operator activity on CV. Primavera, which is engaged in garments, especially in the fabric cutting Laser. section, is a fabric cutting process that uses high-power laser technology that is emitted from a generator on the workpiece, the cutting movement is controlled through a computer so that the possibility of slipping is small. During the cutting laser process, workers stand in front of the cutting laser machine and bend over while setting the fabric size according to the basket. These complaints arise due to non-ergonomic work postures causing pain in some parts of the body felt by workers. The purpose of this study was to determine the level of risk and the percentage of complaints felt during cutting laser. The methods used are Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM), based on the REBA method the work risks faced by workers in cutting laser cloth with a high level of scores in the range of 8-10, high category of action so it needs to be done immediately improvement of work posture. The Nordic Body Map shows the first body segment on the back with a score of 9, the second body segment on the right shoulder with a score of 8, the third body segment on the waist with a score of 8, the fourth body segment on the buttocks with a score of 8, and the fifth body segment on the legs. right with a score of 8, due to a bent work posture during the cutting laser process and fabric size settings as well as age and length of work factors that also affect the questionnaire.